On the RF heating of coronary stents at 7.0 Tesla MRI. Issue 4 (7th October 2014) - Winter, Lukas; Oberacker, Eva; Özerdem, Celal; Ji, Yiyi; von Knobelsdorff‐Brenkenhoff, Florian; Weidemann, Gerd; Ittermann, Bernd; Seifert, Frank; Niendorf, Thoralf
<x xml:space="preserve">Abstract</x> Purpose Examine radiofrequency (RF) induced heating of coronary stents at 7.0 Tesla (T) to derive an analytical approach which supports RF heating assessment of arbitrary stent geometries and RF coils. Methods Simulations are performed to detail electromagnetic fields (EMF), local specific absorption rates (SAR) and temperature changes. For validation E‐field measurements and RF heating experiments are conducted. To progress to clinical setups RF coils tailored for cardiac MRI at 7.0T and coronary stents are incorporated into EMF simulations using a human voxel model. Results Our simulations of coronary stents at 297 MHz were confirmed by E‐field and temperature measurements. An analytical solution which describes SAR(1g tissue voxel) induced by an arbitrary coronary stent interfering with E‐fields generated by an arbitrary RF coil was derived. The analytical approach yielded a conservative estimation of induced SAR(1g tissue voxel) maxima without the need for integrating the stent into EMF simulations of the human voxel model. Conclusion The proposed analytical approach can be applied for any patient, coronary stent type, RF coil configuration and RF transmission regime. The generalized approach is of value for RF heating assessment of other passive electrically conductive implants and provides a novel design criterion for RF coils. Magn Reson Med 74:999–1010, 2015. © 2014 Wiley Periodicals, Inc.